Documenting ethnobotanical knowledge of rural community for sustainable benefits / Jovita Elderson Ripen and Gabriel Tonga Noweg - Ripen, Jovita Elderson; Noweg, Gabriel Tonga (Universiti Teknologi MARA Cawangan Sarawak, 2017)
A study was conducted to identify and document all plants with economic and cultural significance to the nine Singai Bidayuh communities (villages) around the foothills of Mount Singai. Key informant surveys were carried out in each of the villages prior to field documentation and collection of specimens for identification. The information on use and methods of preparations and applications were obtained from active practitioners or traditional “medicine men” and “medicine women” through interviews and application observations for medicinal plants. For each of the plant species identified, specific use, parts of the plant used, method of preparation and applications, and general precautionary notes were included. A total of 52 species of useful plants were documented for medicine and the remaining were for food, preservatives, and spiritual healing. A use and valuation survey on these plant species also revealed that the total value of traditional medicinal plant use for the Singai Bidayuh community based on the current rate of household participation of 10% is at RM15, 443.90 per year. The results have provided a baseline on the economic value of the forest resources and contributed towards a better management of the area as a community heritage.